The Impact of the Emo-Sisi Board Game on Emotional Self-Regulation in Preschool Children: A Quasi Experimental Study - Mustapa, Noviana; Risnawati, Erna; Syarah, Erie Siti; Pramitasari, Muktia; Mahamud, Samihah (Universitas Mercu Buana Jakarta, 2025)
Emotional self-regulation plays an essential role within early childhood education, laying the groundwork for children to cope with emotions and build healthy interactions with others. This research analyses the improvement of preschool aged children’s emotional self-regulation using a quantitative quasi-experimental approach with a pre-test post-test group design with the Emo-Sisi “Understanding Emotion” Board Game. Emo-Sisi Board Game, by Watiek Ideo is an interactive educational game for preschoolers to identify, understand, and regulate emotions. The sample included 50 preschool children, 25 in an intervention group who engaged in structured board game sessions and 25 in a control group who received standard classroom activities. PreBERS scale was utilized to assess emotional self-regulation via pre-test as well as post-test measures. Two-tailed paired independent t- tests and the Wilcoxon signed rank test were used to analyse data. The results demonstrated that the intervention group performed significantly better than the control group on emotional recognition, emotional expression, and application of self-regulation strategies. These insights indicate that the Emo-Sisi Board Game helps to enhance emotional self-regulation skills for preschool children. Future studies are warranted to explore the long-term consequences of these interventions and their effects on wider developmental domains.